2011 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--17793
|View full text |Cite
|
Sign up to set email alerts
|

Does Student Access to Solution Manual Pose a Challenge?

Abstract: Homework problems are assigned to give students the educational experience of solving problems without having access to their solutions and engineering textbooks provide excellent problem sets for homework assignments. Publishers supply solution manuals as a resource for the instructors, with most manuals providing detailed solutions for each problem in the textbook. Since most engineering textbooks solution manuals are currently in digital format, they are readily available to students. This paper provides in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 3 publications
(3 reference statements)
0
14
0
Order By: Relevance
“…Assessing student knowledge has been a major challenge during the pandemic. A sharp increase in cheating was detected in recent years [10][11][12][13]. Scholastic dishonesty includes copying solution manuals for homework assignments, using phones, text, and apps to share answers; using phones to take images of exam questions, sending them to external tutoring services, and copying solutions received from the external tutoring services.…”
Section: Examsmentioning
confidence: 99%
“…Assessing student knowledge has been a major challenge during the pandemic. A sharp increase in cheating was detected in recent years [10][11][12][13]. Scholastic dishonesty includes copying solution manuals for homework assignments, using phones, text, and apps to share answers; using phones to take images of exam questions, sending them to external tutoring services, and copying solutions received from the external tutoring services.…”
Section: Examsmentioning
confidence: 99%
“…Over ninety percent of students use textbook solution manuals in completing their homework assignments. The rates of students admitting to cheating during their college education has increased from 26% in 1963 to 54% in 1993 [7]. That percentage is much higher today.…”
Section: Proceedings Of the 2016 Asee Gulf-southwest Annual Conferencementioning
confidence: 99%
“…However with the availability of digital copies of the textbook solution manuals since the early 2000, student use of engineering textbook solution manuals in doing homework assignments has dramatically increased. Several studies have reported on this topic [7][8][9][10][11][12][13].…”
Section: Proceedings Of the 2016 Asee Gulf-southwest Annual Conferencementioning
confidence: 99%
See 1 more Smart Citation
“…Students learn that they must simply look in the previous pages for the "right equation" apply it correctly and find the "right answer." The proliferation of online solution manuals also corrupts the process allowing students to see the entire solution without the effort of synthesizing the course material 4,5 . Although solving a wide variety of problems gives students more practice and may illustrate more concepts, it does not encourage students to go in depth on any one problem, apply critical thinking or conduct outside research.…”
Section: Introductionmentioning
confidence: 99%